Ulam-Hyers Stability Results of λ-Quadratic Functional Equation with Three Variables in Non-Archimedean Banach Space and Non-Archimedean Random Normed Space. (20th May 2022) - Van An, Ly; Tamilvanan, Kandhasamy; Udhayakumar, R.; Kabeto, Masho Jima; Van Ngoc, Ly
Abstract : In this paper, we introduce the λ -quadratic functional equation with three variables and obtain its general solution. The main aim of this work is to examine the Ulam-Hyers stability of this functional equation in non-Archimedean Banach space by using direct and fixed point techniques and examine the stability results in non-Archimedean random normed space.